Effects of a new dietary supplement on behavioural responses of dogs exposed to mild stressors. Issue 5 (8th July 2021) - Titeux, Emmanuelle; Padilla, Stephanie; Paragon, Bernard‐Marie; Gilbert, Caroline
Abstract: Background & Objectives: The effectiveness of a new dietary supplement (derived from fish hydrolysate and melon juice concentrate rich in superoxide dismutase) in reducing fear and stress‐related behaviours in pet dogs was examined in a double‐blind, placebo‐controlled, randomized study. Methods: 39 dogs were recruited after the owners had filled out a fear susceptibility index questionnaire. Over a 30‐day period, one group of dogs received the supplement, and another group a placebo. Twelve behavioural variables were recorded in a series of four subtests (ST1‐ST4) on days 0, 15 and 30. Saliva cortisol levels were measured before and after each set of STs. Results: The dogs rated as more fearful displayed significantly higher cortisol values before the day 0 test session, were less active, spent less time playing with the experimenter, and approached the unfamiliar object less frequently. The owners did not correctly guess whether their dog had received the supplement or not. Behaviours of dogs were significantly different across the three sessions, with significant increases of stress‐related behaviours (time spent in the door zone, number of interactions with the door, of whining, and of lip‐licking). Conversely time spent with the experimenter increased, interactions and curiosity for the novel object and play with the experimenter decreased, presumably due to a habituation process. This suggests that the design of the four subtests session was relevant to test for mild stressors situations. Moreover, supplemented and placebo dogs responded differently to the three test sessions, indicating a supplement effect on dogs' behaviours and their adaptation to mild stressors situations. Conclusion: The trial results suggested that the supplement facilitates activity and curiosity in a familiar environment, promotes dog‐human interactions with an increased human familiarity, and tends to reduce subtle stress behaviours. Our results suggest that the supplement was effective in the context of mild stressors and habituation. Abstract : In a double‐blind, randomized study, dogs received either a new supplement or a placebo for 30 days; the two groups were compared in a series of four behavioral tests. The behavioral tests were designed to mimic everyday life stressors and were applied on days 0, day 15 and day 30 to selected dogs. The dogs in the supplement group displayed an increased activity, greater familiarity with a stranger. This suggests that learning processes had been enhanced. Our results suggest that when combined with behavioral therapy, the new supplement might be useful in reducing mild fear and stress reactions in a context of everyday life stressors.